Liver lipid droplet cholesterol content is a key determinant of metabolic dysfunction–associated steatohepatitis - Ikki Sakuma; Rafael C. Gaspar; Ali R. Nasiri; Sylvie Dufour; Mario Kahn; Jie Zheng; Traci E. LaMoia; Mateus T. Guerra; Yuki Taki; Yusuke Kawashima; Dean Yimlamai; Mark Perelis; et al. (Proceedings of the National Academy of Sciences, 2025)
Metabolic dysfunction–associated steatohepatitis (MASH) represents a progressive form of steatotic liver disease which increases the risk for fibrosis and advanced liver disease. The accumulation of discrete species of bioactive lipids has been postulated to activate signaling pathways that promote inflammation and fibrosis. However, the key pathogenic lipid species is a matter of debate. We explored candidates using various dietary, molecular, and genetic models. Mice fed a choline-deficient L-amino acid–defined high-fat diet (CDAHFD) developed steatohepatitis and manifested early markers of liver fibrosis associated with increased cholesterol content in liver lipid droplets within 5 d without any changes in total liver cholesterol content. Treating mice with antisense oligonucleotides against Coenzyme A synthase ( Coasy ) or treatment with bempedoic acid or atorvastatin decreased liver lipid droplet cholesterol content and prevented CDAHFD-induced MASH and the fibrotic response. All these salutary effects were abrogated with dietary cholesterol supplementation. Analysis of human liver samples demonstrated that cholesterol in liver lipid droplets was increased in humans with MASH and liver fibrosis and was higher in PNPLA3 I148M (variants rs738409) than in HSD17B13 variants (rs72613567). Together, these data identify cholesterol in liver lipid droplets as a critical mediator of MASH and demonstrate that Coenzyme A synthase knockdown and bempedoic acid are therapeutic approaches to reduce liver lipid droplet cholesterol content and thereby prevent the development of MASH and liver fibrosis.